Analisis Model Kano pada Rancang Bangun Game Belajar Bahasa Inggris Berbasis Android pada Sekolah Dasar - Feoh, Gerson; Agustia, Komang Tri Sutrisna; Amadea, Ida Bagus Neo Kurnia (Jurnal Informatika Terpadu, 2024)
The English learning process at SDN 5 Gulingan is still monotonous and uninteresting, resulting in low student interest and motivation. This has led to efforts to increase student engagement and participation through the implementation of gamification. This research aims to develop and implement gamification in the English learning process at SDN 5 Gulingan and measure the level of user satisfaction with the gamification features implemented. This research uses the ADDIE model in gamification development, which includes the stages of analysis, design, development, implementation, and evaluation. The Kano model is used to measure the level of user satisfaction with gamification features. The results show that gamification features, such as points, badges, leaderboards, and quiz features, can increase students' interest and motivation to learn. These features also help students understand the learning material more easily and enjoyably. The implementation of gamification in the English learning process at SDN 5 Gulingan proved to be effective in increasing students' interest, motivation, and learning effectiveness. This shows that gamification can be a solution to overcome the problem of monotonous and uninteresting learning.